Characteristics and needs of physical and mental health among older adult individuals with disabilities under the background of smart healthcare: according to data from the China family panel studies - Zou, Qianlingzi; Guan, Xin; Cao, Xiaojing; Gu, Huangying; Wang, Caimeng; Ming, Xin; Li, Rongyong (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to utilize data from the China family panel studies (CFPS) to systematically analyze the physical and mental health characteristics and needs of older adult individuals with disabilities under the context of smart healthcare, aiming to provide scientific evidence for relevant policy formulation.MethodsData were derived from the CFPS surveys conducted by Peking University’s China Social Sciences between 2021 and 2022. Older adult individuals aged 65 and above requiring assistance in activities of daily living (ADL) or instrumental activities of daily living (IADL) were included. Descriptive statistics, univariate analysis, and multivariate analysis were employed to analyze the basic characteristics, physical and mental health status, influencing factors, and corresponding needs of older adult individuals with disabilities.ResultsSamples aged between 65 and 80, widowed or divorced, demonstrated higher physical health scores (p < 0.05); samples with education at college level or above, residing in urban areas, free from chronic diseases, with annual income exceeding 100,000 RMB, receiving daily family support, frequently accessing community services, and regularly using smart medical devices exhibited greatly higher levels of physical health, mental health, and overall scores on the short form health survey (SF-36) (p < 0.05). Factors such as younger age, absence of chronic diseases, higher economic status, daily family support, frequent access to community services, and regular use of smart medical devices exerted favorable effects on the physical health status of older adult individuals with disabilities (p < 0.05); absence of chronic diseases, urban residence, higher economic status, daily family support, and frequent access to community services were found to positively influence the mental health status of older adult individuals with disabilities (p < 0.05).ConclusionThe physical and mental health status of older adult individuals with disabilities is influenced by various factors, including social support, economic conditions, and utilization of medical resources. These factors constitute significant determinants in improving the physical and mental health of older adult individuals with disabilities and represent key needs for their betterment.